IMMIGRATION SOCIALIZATION TOWARDS AWARENESS AND ACTIVE COMMUNITY PARTICIPATION: CASE STUDY AT CLASS I IMMIGRATION OFFICE TPI BANDA ACEH - A ARISMAN; Nurul Maharani Piranti (Polteknik Imigrasi, 2022)
TPI Banda Aceh Class I Immigration Office plays an important role in managing the flow of people moving across countries and ensuring national security. In this context, immigration socialization is crucial to provide understanding to the public about immigration procedures, regulations, and their impacts. The purpose of this outreach is to increase public awareness about the importance of understanding immigration regulations, provide up-to-date information, reduce misunderstandings, encourage active community participation, and build better cooperation between the Immigration Office and the community. In this endeavor, a diverse and targeted outreach program will be organized through interactive sessions, workshops and mass media with support from local communities and educational institutions. Through this outreach, it is hoped that an environment that is inclusive, aware of regulations, and participatory will be created, will have a positive impact in facilitating legal and safe international travel, and building a better society in Banda Aceh.